Reproduction and Development of Sitophilus granarius L. (Coleoptera Curculionidae) in Different Wheat Varieties (Bollettino di zoologia agraria e bachicoltura, 2024)
Oviposition and development of the emergent Sitophilus granarius L. have been studied on six different grain varieties: Adria, Fiorello, Gemini, Manital, Orso, Salmone.This paper points out that wheat variety does not influence:I) female fecondity;2) laid eggs number in each grain, ranging from I to 6.On the contrary wheat variety influences:1) infested grain number;2) larval development velocity, as proved by the adult number emerged within 57 days from the onset of the experiments. In addition larval development velocity is not in relation with the grain weight.lt can be concluded that different varieties of wheat grain affect the development of S. granarius, probably owing to his feeding necessity.
Keywords: Sitophilus granarius; reproduction; wheat varieties